On the orientation effect of the neutron yield increase in d(d, n)3H? reactions at an energy of 7–12 keV in TiD2 crystals; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 11, iss. 3 - Bystritsky V. M. Vyacheslav Mikhaylovich; Dudkin G. N. Gennadiy Nikolaevich; Kuznetsov S. I. Sergey Ivanovich; Pivovarov Yu. L. Yuriy Leonidovich; Tukhfatullin T. A. Timur Ahatovich; Nevedomsky V. A. Vladislav Andreevich (2017, 2017)
Title screen